Developing a Book for Teaching Reading Skills in the Context of Local Culture: The Department of Arabic Language Teaching at Indonesia University | Tathwir Kitab li-Ta'lim Maharat al-Qira'ah fi Siyaq al-Thaqafah al-Mahalliyyah: Qism Ta'lim al-Lughah al-'Arabiyyah fi Jami'ah Indonesia - Suwandi Suwandi; Sutaman Sutaman; M. Samsul Ulum; Diaya Uddeen Deab Mahmoud Alzitawi; Supangat Supangat (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
Students do not have a specific book for learning maharah qiro